Mood disorder following traumatic brain injury: a case report - Koparal, Buket; Coşar, Behçet (The European Research Journal, 2019)
Traumatic brain injury is a clinical situation that generally affects young people aged 45 years or younger and causes mortality and critical functional losses. The most common psychiatric disorder following taumatic brain injury is depression. Although the relationship between depression and organic diseases has been studied a lot, there is less data about mania. Secondary mania differs from primary mania with advanced beginning age, absence of family history, more difficult and slower response to treatment; and secondary mania usually has no recurrence. In this report, secondary mania and its clinical features are discussed in light of a mood disorder following a trauma case. The case is still followed with mood stabilizer treatment and the patient is euthymic.